ChemInform Abstract: Nickel—NHC‐Catalyzed Cross‐Coupling of 2‐Methylsulfanylbenzofurans with Alkyl Grignard Reagents. Issue 27 (18th June 2015) - Baralle, Alexandre; Otsuka, Shinya; Guerin, Vincent; Murakami, Kei; Yorimitsu, Hideki; Osuka, Atsuhiro
Abstract The efficient method is applied in the synthesis of protein tyrosine phosphatase inhibitors of type (VI).